Soybean is a good source of protein. It has two major fractions, b-conglycinin (7S) and glycinin (11S). b-conglycinin’s function was known to suppress food intake, and this effect may be due to stimulating endogenous cholecystokinin (CCK) release. The aims of this study were to determine the highest content of total b-conglycinin and b-conglycinin sub unit-b level obtained from two varieties of soybean i.e. Wilis and Detam 1 varieties using different preparation and extraction methods. These two - MEILINAH HIDAYAT; MUCHTAN SUJATNO; NUGRAHA SUTADIPURA; . SETIAWAN; AHMAD FARIED (HAYATI Journal of Biosciences, 2011)
Soybean is a good source of protein. It has two major fractions, b-conglycinin (7S) and glycinin (11S). b-conglycinin’s function was known to suppress food intake, and this effect may be due to stimulating endogenous cholecystokinin (CCK) release. The aims of this study were to determine the highest content of total b-conglycinin and b-conglycinin sub unit-b level obtained from two varieties of soybean i.e. Wilis and Detam 1 varieties using different preparation and extraction methods. These two soybean varieties were prepared into tempeh. Then the seed and tempeh were extracted using Deak and Panthee methods. There were six extracts analysed using sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS PAGE) and coomassie brilliant blue (CBB) staining. The result was shown that Detam variety and raw seed contained the highest total b-conglycinin level. And Panthee method was the best method for extraction of total b-conglycinin, while Deak method was the best method for extraction of b-conglycinin subunit-b.